Критеріальний підхід до пошуку струмових режимів роботи термоелектричних пристроїв підвищеної надійності - Zaikov, V. P.; Meshcheryakov, V. I.; Zhuravlyov, Yu. I. (PE "Politekhperiodika", Book and Journal Publishers, 2017)
The authors consider possibilities of the criterial approach to determining the current operating mode of a single-stage thermoelectric cooling unit (TCU), when used reliability failure rate as a basic parameter. The relations were obtained for determining the current operating mode of a TCU with a given geometry of the branches for different operating conditions, taking into account a variety of restrictive requirements. The paper presents a comparative analysis of current conditions close to the maximum energy efficiency and minimum mode's failure rate, which allows choosing compromise options.